2016
DOI: 10.1111/jsbm.12248
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Crisis and Sustainable Reorganization: Evidence from Bankrupt Austrian SMEs

Abstract: Bankruptcy and failure continue to affect small and medium‐sized enterprises (SMEs) worldwide. Since bankruptcies are costly and disruptive, it seems useful to identify factors and resources that are essential for SMEs to overcome a crisis and to reorganize in a way that leads to a sustainable and lasting renewal. By drawing on longitudinal data, we identified essential elements of sustainable reorganization of bankrupt SMEs in Austria that ensure long‐term survival and competitiveness. The results of our stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(116 citation statements)
references
References 95 publications
2
100
0
1
Order By: Relevance
“…We also classified the studies we investigated by continent (Figure ). Most of the research studies we have found occur in Europe, which makes up 41% of the research (e.g., Girgenti, Peano, Baudino, & Tecco, ; Hertel & Menrad, ; Flynn & Davis, ; Jansson, Nilsson, Modig, & Hed Vall, ; Mayr, Mitter, & Aichmayr, ; Torkkeli, Kuivalainen, Saarenketo, & Puumalainen, ; Girella, Zambon, & Rossi, ), Asia accounts for 22% (e.g., Seth, Rehman, & Shrivastava, ; Singh, Olugu, & Musa, ) and South America at 19% (e.g., Lucato, Costa, & de Oliveira Neto, ; Pacheco, Caten, Jung, Navas, & Cruz‐Machado, ; Sarango‐Lalangui, Álvarez‐García, & del Río‐Rama, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also classified the studies we investigated by continent (Figure ). Most of the research studies we have found occur in Europe, which makes up 41% of the research (e.g., Girgenti, Peano, Baudino, & Tecco, ; Hertel & Menrad, ; Flynn & Davis, ; Jansson, Nilsson, Modig, & Hed Vall, ; Mayr, Mitter, & Aichmayr, ; Torkkeli, Kuivalainen, Saarenketo, & Puumalainen, ; Girella, Zambon, & Rossi, ), Asia accounts for 22% (e.g., Seth, Rehman, & Shrivastava, ; Singh, Olugu, & Musa, ) and South America at 19% (e.g., Lucato, Costa, & de Oliveira Neto, ; Pacheco, Caten, Jung, Navas, & Cruz‐Machado, ; Sarango‐Lalangui, Álvarez‐García, & del Río‐Rama, ).…”
Section: Resultsmentioning
confidence: 99%
“…We also classified the studies we investigated by continent ( Figure 4). Most of the research studies we have found occur in Europe, which makes up 41% of the research (e.g., Girgenti, Peano, Baudino, & Tecco, 2014;Hertel & Menrad, 2015;Flynn & Davis, 2016;Jansson, Nilsson, Modig, & Hed Vall, 2017;Mayr, Mitter, & Aichmayr, 2017;Torkkeli, Kuivalainen, Saarenketo, & Puumalainen, 2019;Girella, Zambon, & Rossi, 2019), Asia accounts for 22% (e.g., Seth, Rehman, & Shrivastava, 2018;Singh, Olugu, & Musa, 2016) and South America at 19% (e.g., Lucato, Costa, & ables on which SMEs can be categorized (Bar, 2015;Boiral, Ebrahimi, Kuyken, & Talbot, 2019;Groot et al, 2019;Long, Looijen, & Blok, 2018;Malesios et al, 2018;Prieto-Sandoval, Ormazabal, Jaca, & Viles, 2018). Our results show the pattern in the sectors that are studied from 2013 to 2019 (Figure 7).…”
Section: And Eco-friendly and Driversmentioning
confidence: 99%
“…They verify a positive relationship between proenvironmental strategies and competitiveness in a case ( Despite the critical nature of the issue, only few articles include the economic crisis in their analysis and attempt to identify essential factors and resources for SMEs to overcome a crisis. However, they identify that a strategic repositioning is the most influential factor in overcoming a crisis and achieving a sustainable turnaround (Mayr, Mitter, & Aichmayr, 2017;Panwar, Nybakk, Pinkse, & Hansen, 2015).…”
Section: Final Dataset 62mentioning
confidence: 99%
“…Furthermore, the existence of contexts where the SMEs represent over 90% of the entire economic system denotes their central role in the mechanisms connected to the financial crisis. The central role of the SMEs is related to their high degree of financial dependence on external stakeholders like suppliers and clients (Mayr, Mitter, & Aichmayr, ). In this sense, the negative effects of a bankruptcy impact the entire local economic system (Herbane, ).…”
Section: Introductionmentioning
confidence: 99%